PENGARUH LEVERAGE, SAHAM PUBLIK, SIZE DAN KOMITE AUDIT TERHADAP LUAS PENGUNGKAPAN SUKARELA - -, Mujiyono; Nany, Magdalena (Jurnal Dinamika Akuntansi, 2010)
Tujuan dari penelitian ini adalah memberikan bukti empiris mengenai efek leverage, saham publik, size, proporsi komite audit independen pada pengungkapan sukarela baik secara partial maupun simultan. 74 perusahaan telah dianalisis dengan menggunakan analisis multiple regression. Hasilnya menunjukkan bahwa leverage secara tidak signifikan mempunyai efek negatif pada pengungkapan sukarela begitu juga dengan saham publik, size dan proporsi komite audit independen yang tidak signifikan pada pengungkapan sukarela.ÃÂ The objective of this research is to give empirical evidence about the effects of leverage, public ownership, size, and independent audit committee proportion on voluntary disclosure both partially and simultaneously. Seventy four companies were analyzed by using multiple regression analysis. The results show that leverage insignificantly has negative effect on voluntary disclosure. Public ownership also insignificantly has negative effect on voluntary disclosure. But size significantly has positive effect on voluntary disclosure. Independent audit committee proportion insignificantly has negative effect on voluntary disclosure. The result also shows that leverage, public ownership, size and independent audit committee proportion simultaneously have insignificant effect on voluntary disclosure.